Matrimonial situation of the Rivne region in the mirror of all-Ukrainian and pan-European trends - Oksana Romaniv; Andriy Romaniv; Alla Onopriychuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2017)
The Rivne Region has higher rates of marriages and lower rates of divorces than the average in Ukraine, but these trends diminish gradually. In the future, a general trend of growth in the index of marriage stability and its decrease in the Rivne Region can be anticipated due to the fact that marriage rates in the oblast will continue to decline while divorce rates will increase insignificantly. The most typical deformations and structural changes in the matrimonial behaviour of the population of the Rivne Region include: the strengthening of the trends of decrease in marriage rates and increase in divorce rates, the probable growth in the frequency of consensual marriages, the spread of extramarital motherhood and the rise of the average marital age. The conclusion can be made that at the current stage, the family in the Rivne Region continues to fulfil its main functions overall: birth, raising and maintenance of children. Despite the new trends in the development of institutions of marriage and family, the way of performance of the special functions of the family remains traditional: the vast majority of children are born within a registered marriage. However, there are socio-demographic phenomena whose contemporary scales testify to the adverse conditions in which families exist. In particular, the numbers of orphans and children deprived of parental care grows.